Pizhūhishhāʾī dar tārīkh-i ʿilm : Maqālātī dar bāra-yi tārīkh-i riyāḍiyyāt, nujūm, mikānīk, wa pizishkī - Chāvushī, Jaʿfar Āqāyānī,; Chāwushī, Jaʿfar Āqāyānī, (Miras Maktoob, ISBN: 9789004365452., 2019)
As is well known, large parts of the Greek sciences were assimilated by the medieval Muslim world. Equally well known is the fact that quite a number of Muslim scholars contributed to the further development of some of these sciences and also, that some of their works were translated into Latin and other western languages, leaving their imprint on late medieval and early modern science in turn. For this reason, anyone interested in the history of science in the western world will be interested in reading about the history of science in Islam and vice versa. This is why the editor of the present collection of articles has done well to bring together contributions from both fields, in French, English, and Persian. While all of these articles are interesting in their own right, the section dedicated to Naṣīr al-Dīn Ṭūsī (d. 672/1274) and a study of Descartes' (d. 1650) de Solidorum elementis deserve special mention.